INSECTOS ACUÁTICOS QUE COLONIZAN AMBIENTES CREADOS POR EL HOMBRE EN URUGUAY - Martínez, María; Willat, Gabriela; Guerrero, José Carlos; Emmerich, Daniel (Boletín de la Sociedad Zoológica del Uruguay, 2017)
This study was conducted under the «National Plan of Detection and Control of Aedes aegypti (Linnaeus, 1762) in Uruguay,» from 1997 to 2012. Diversity of aquatic insects found in artificial containers and household drains in Uruguay is documented. Different types of containers used as breeding sites and their associated aquatic fauna is detailed. Five orders were collected: Diptera, Ephemeroptera, Odonata, Hemiptera and Coleoptera. Dipterans were the most diverse, represented by nine families: Ceratopogonidae, Chironomidae, Corethrellidae, Culicidae, Ephydridae, Phoridae, Psychodidae, Syrphidae and Tipulidae. The species identified were: Dasyhelea necrophila Spinelli & Rodriguez, 1999 Chironomus (Chironomus) calligraphus Goeldi, 1905, Corethrella sp., complex Megaselia imitatrix, Clogmia albipunctata (Williston, 1893), Psychoda (Tinearia) alternata Say, 1824, Psychoda cinerea Banks, 1894, Callibaetis sp., Sigara sp., Buenoa sp., Notonecta sp., Liodessus sp., Rhantus sp. and Thermonectus sp. In this paper Culicidae species are not included because they were presented in a previous publication.